Análise de esforços resultantes de impactos entre barcaças de comboios fluviais para modelagem de um sistema de amortecimento de choques utilizando teoria de análise multicorpos - CRUZ, Fernando Costa da (Universidade Federal do Pará, 2022)
In this dissertation an analysis is performed on the operational behavior of river barges convoys in navigation regions with presence of waves, winds and currents. A study is carried out to determine the applicant forces present in the mooring elements and in the contact points between barges in flotillas when they are sailing in dangerous navigation conditions. A theoretical study is carried out, identifying the main response movements of floating bodies. In this case, a model is developed using the ANSYS AQWA 17 software to identify the stress levels from impacts between barges that make up the formations, as well as the degree and behavior of the tensile stresses present in the mooring ropes over time. In addition, a practical study is used as a comparative model of data, being very important for the validation of the results achieved by the computational model. In this way, the proposed scenario within the computational program describes environmental characteristics to describe the navigation problem in a clear way. At the end of this work the levels of effort captured within the computational model are presented, being divided into two models of fluvial flotillas, a convoy with barges for soybean transportation, and another with barges for the transport of iron ore, being discriminated the locations of the higher levels of effort. It is important to note the pioneering role of this work in relation to the problems perceived within the area of operational safety of fluvial flotillas, using Finite Element tools as the main evaluation tool.